(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to determine the effect of financial ratios represented by liquidity ratios, profitability ratios and market ratio to solvency ratios in agricultural sector companies listed on the Indonesia Stock Exchange 2015-2019 period either simultaneously or partially. The results showed that simultaneously the liquidity ratio, profitability ratio and market ratio had an effect on the solvency ratio. Partially, the liquidity ratio and the profitability ratio have an effect on the solvency ratio, while the market ratio has no effect on the solvency ratio. The suggestion for this research is that the company, when maintaining its solvency ratio, also maintains the liquidity ratio and profitability ratio. The advice for investors is that when focusing on market ratios, there is no need to pay too much attention to solvency ratios. The last suggestion is for other researchers to add other variables that affect the solvency ratio.